Environmental education experiences in the Biology cathedra the UCLA agro-industrial engineering (Agroindustria, Sociedad y Ambiente, 2022)
Environmental education is a permanent process in which individuals and communities acquire awareness of the environment and develop values, skills and experiences for the preservation of the environment. The development of activities within the academic content of the chair of Biology of the Agroindustrial Engineering Program of the Lisandro Alvarado Centroccidental University ”, had as main objective to sensitize students of the third semester of environmental problems, through the application of educational and recreational activities in the university headquarters and the Pablo Manzano Veloz Bolivarian Primary School (EPBPMV). The activities were developed during 4 continuous academic periods, where work groups were organized with the enrollment of students and they were assigned a theme and educational activity related to the environment. Said topics were: generalities about the environment and its conservation, Importance and conservation of water, importance and conservation of plants and animals; management, classification and use of waste, recycling, pollution and energy saving. As a result of the experiences and activities we have: creation of an Environmentalist Brigade of university students and primary school students, rescue and planting of ornamental, forest and fruit plants in abandoned spaces in the university nucleus, development of a forest plant nursery (Mahogany, Carocaro and Samán), fruit trees (tamarind, soursop, semeruco), containing approximately 800 plants in the EPBPMV facilities, together with the environmental brigade made up of 4th and 5th grade students from the campus. A total of 120 students from UCLA and 500 children from EPBPMV were sensitized.
Keywords: Environmental education; recycling; nursery